Design of virtual laboratory media based on HTML 5 Canvas and graphical user interface in physics learning - Zulkarnain, Zulkarnain; Utami, Linda Sekar; Sabaryati, Johri; Islahudin, Islahudin; Subhan, Subhan; Arisandi, Dea (Yayasan Indonesia Emerging Literacy Education, 2024)
Physics is an important part of the science curriculum at both the high school and college levels. Physics learning requires students to master abstract theoretical concepts, so it is not uncommon for these theoretical concepts to be difficult for learners to perceive. Abstract concepts in physics learning can be overcome through practical activities in concrete laboratories or virtual laboratories. This study aims to produce virtual laboratory media based on HTML 5 Canvas and Javascript programs packaged in Graphical User Interface (GUI) format in terms of experts, practicioners, and students. The research method used is research and development (R&D), using the 4D model (Define, Design, Develop, and Disseminate). The subjects were conducted in second-years physic students which consisted of 8 students (small group test) and in class XI high school students which consisted of 20 students (large group test). The instrument used were interview sheets, documentation, and questionnaires. The data were analyzed using descriptive analysis techniques. The results showed that virtual laboratory media was valid with a CVI score of 0,87 and reliable with a Percentage of Agreement score of 85,95% based on experts and practitioners judgment. In addition, based on the results of the practicality test for students, the test results were in the very practical category with a practicality score of 86,4% and 88,6% respectively for small group test and large group test. So it can be concluded that virtual laboratory media can be used to support physic learning.